Effectiveness of professional-identity-formation and clinical communication-skills programs on medical students’ empathy in the COVID-19 context: comparison between pre-pandemic in-person classes and during-pandemic online classes - Hitomi Kataoka; Akiko Tokinobu; Chikako Fujii; Mayu Watanabe; Mikako Obika (BMC Medical Education)
Abstract Background Enhancing students’ empathy is critical in medical school education. The COVID-19 pandemic necessitated a shift from in-person to online classes. However, the effectiveness of online classes for enhancing medical students’ empathy has not been investigated sufficiently and the evidence is limited. This study compared the effectiveness of enhancing empathy between pre-pandemic in-person classes and during-pandemic online classes among medical students in Japan using pre-pandemic and during-pandemic data. Methods This is a retrospective observational study. This study measured students’ empathy using the Japanese translation of the Jefferson Scale of Empathy-Student Version (JSE-S) before and after the special programs for professional identity formation and clinical communication among first- and second-year students who matriculated from 2015–2021. This study categorized the matriculation year groups as “pre-pandemic” and “during-pandemic” groups for the first- and second-year students. This study estimated the adjusted mean score differences of the JSE-S and 95% confidence intervals (CIs) from the pre- to post-program between the pre-pandemic and during-pandemic groups in the first and second years using linear regression analysis. Results This study’s participants included 653 first-year students and 562 second-year students. In the first year, the during-pandemic group had a significantly higher mean score difference from the pre- to post-program compared to the pre-pandemic group. The adjusted regression coefficient (95% CI) was 7.6 (5.7 – 9.5), with the pre-pandemic group as the reference. In the second year, there were no significant differences between the two groups. Conclusions The results suggest that online classes are not inferior to in-person classes or even slightly better in enhancing medical students’ empathy, which should be clarified by further studies. This study’s findings have important implications for medical education and implementing hybrid class formats to enhance students’ empathy.